Cultural Development on Peranakan Chinese a Thematic Review: A thematic review - Huang, Wenhong; Ahmad Rizal Abdul Rahman; Sarjit Singh Darshan Singh; Raja Ahmad Azmeer Raja Ahmad Effendi (Advances in Humanities and Contemporary Studies, 2024)
The Peranakan Chinese culture is a unique sample of multicultural amalgamation, and its intricate nature has spurred scholarly discussions for decades. As modern society evolves, opportunities and challenges arise for its cultural conservation. Nevertheless, However, there is a distinct lack of comprehensive review on this subject globally. To address this gap, utilizing the ATLAS. ti 23 software, this paper undertakes a thematic review of 30 articles related to Peranakan Chinese culture published between 2018 and August 2023. Through thematic analysis, five core themes emerge: Cultural Identity, Cultural Conservation, History and Society, Tangible and Intangible Cultural Heritage, and Cultural Dissemination. While diversity is widely recognised as a hallmark of Peranakan Chinese culture, this study sheds further light on the nuances and complexities of cultural integration due to geographic, historical and social factors. The review observes that current research predominantly validates past perspectives on cultural identity by examining various cultural mediums across different branches. However, there is a gradual shift towards sustainable cultural development. Moreover, the study underscores the significance of exploring new technologies and concepts for cultural conservation. This research offers direction for researchers interested in Peranakan Chinese and provides insights for deeper investigations into the subject.